Case report: Dystonia and athetosis in ICH of 80 years old female patient - Kristiani, Alyn; Sunarnyo, Sunarnyo (Science Midwifery, 2024)
Dystonia is defined as involuntary and persistent contraction of agonist and antagonist muscles resulting in abnormal posture, twisting and repetitive movements, or trembling. These can be initiated or worsened by attempts to make movements. Dystonia is a dynamic disorder whose severity changes based on activity and body posture. Case An 80 years-old woman was brought by her family to the emergency room at RAA Soewondo Regional Hospital, Pati with complaints of movements, such as twisting her arms and legs from the right arm and leg continuously without stopping which appeared since 2 (two) days before entering the hospital. Physical examination revealed continuous voluntary and twisting movements of the right arm and leg. There was a neurological deficit in nerve VII, namely; eyebrows, nasolabial sulcus, and corners of the mouth that deviate to the left. Moreover, there are also neurological deficits in nerve XII, namely; tongue deviation to the left side and tongue deviation during contraction to the right side. Therefore, patients receive inpatient treatment at the hospital. Conclusion: is dystonia is a clinical diagnosis made based on history, observation, and direct examination. Treatment provided depends on the patient's age, diagnosis, and distribution of dystonia, and is individualized, consisting of rehabilitation, botulinum toxin injections, oral pharmacotherapy, and DBS.